Implementation of lifelong learning policy in community colleges in Malaysia - Jantan, Amer Hamzah (2012)
This study looks at the implementation of the lifelong learning policy and its practice in Malaysia. The Malaysian Government has identified Community Colleges as hubs of lifelong learning in 2005. This was done through a Cabinet decision under the Premiership of Tun Abdullah Ahmad Badawi. As hubs of lifelong learning, the role being played by community colleges is crucial in the success of the lifelong learning agenda. Lifelong learning is also one of the main thrusts of the Higher Education Strategic Plan launched by the Ministry of Higher Education. It is also in line with the New Economic Model as espoused by the Government of Malaysia that stresses the importance of the human capital. This study is a qualitative look at the implementation. It looks at the understanding and experiences of lifelong learning among Directors of Community Colleges throughout Malaysia. The directors are policy implementers. Thus, it is of utmost importance that these Directors understand the lifelong learning policy as espoused by the government. The study is an analysis of how policy is understood and how it is being implemented at the community college level. There are 12 informants in this study. Data were gathered through interviews with the informants. One of the informants did not want to be interviewed and chose to reply to the questions via email. Each interview lasted between 20 to 50 minutes. The interviews were conducted in Bahasa Malaysia and were later transcribed verbatim by the researcher. The informants were asked questions related to their understanding of the lifelong learning concept. These include (i) understanding of lifelong learning; (ii) formal, informal and non-formal learning; (iii) the implementation of lifelong learning in Malaysia; (iv) involvement of the people in lifelong learning; (v) motivation to learn; (vi) availability of lifelong learning opportunities; (vii) financial support; and (viii) policy decisions. Findings were clustered into different themes and sub-themes which emerged from the data. These themes and sub-themes show differing views among these Directors on the understanding of lifelong learning and how to implement lifelong learning programs in their respective colleges. These may be due to their different understanding of the lifelong learning concept itself. This study is a first hand account of how first level policy implementers put the lifelong learning policy into practice. The findings reveal constraints in their own understanding of the policy. Thus, the Ministry of Higher Education would need to equip its Directors with the necessary know-how to ensure the success of the lifelong learning agenda. Implications of the findings include the need for a lifelong learning plan; the need to revisit the Cabinet decision in 2005; the coordination of programs and initiatives of various ministries and agencies; the proper selection of the directors as policy implementers; as well as the need for continuous training for the directors. These would be a basic foundation that would be needed to contribute towards the success of the lifelong learning agenda.